(untitled) (Journal of Information Systems and Technology Management, 2009)
The purpose of the research was to analyze the entrepreneurial interest of students in information technology related courses. A literature review was performed, from which four hypotheses were announced, affirming that the student interest in entrepreneurial activity is influenced by (1) the perceived vocation of the area, (2) the ownership of a company, (3) the perceived social support from friends and family, and (4) the entrepreneurial skills mastery. A field study was developed, with data collected from the 171 students of higher education institutions from Fortaleza. The data were analyzed by using statistical techniques of descriptive analysis, analysis of variance, and multiple regression analysis. It was found that: (1) students, in general, have a moderate predisposition to engage in entrepreneurial activities; (2) the entrepreneurial interest is influenced by the perceived entrepreneurial vocation of the area, the social support, and the perceived strategic entrepreneurial skills mastery.